Challenging dominance: the opposition, the coalition and the 2016 election in Uganda. Issue 4 (1st October 2016) - Beardsworth, Nicole
ABSTRACT: Contrary to the experience of many African countries, opposition coalitions are a frequent feature of elections in Uganda. A product of previous alliance efforts and a concerted effort by sections of civil society to facilitate coordination between parties, the 2016 Democratic Alliance was the most cogent collective to date. The broad alliance fragmented just three months before the election as the Forum for Democratic Change pulled out over the selection of the joint presidential candidate. This paper will look at the logic that underlies coalition formation in Ugandan elections, as well as the key reasons for their collapse. This article contends that, when studying coalition formation and collapse, more attention should be given to intra- and inter-party dynamics and competition over shared electoral constituencies, as well as the role of trust, uncertainty and strategic decision-making in successful coalition formation.